Facilitators and barriers to COVID-19 testing in community and clinical settings: Lessons learned from Lesotho and Zambia. - Musonda Simwinga; Palesa A Mahlatsi; Masemote Molale; Gracious Witola; Isaac Mshanga; Bulemba Katende; Alain Amstutz; Klaus Reither; Kwame Shanaube; Masetsibi Motlomelo; Virginia Bond; Jennifer M Belus (Public Library of Science (PLoS), 2023)
The sudden emergence of the coronavirus disease 2019 (COVID-19) had a devastating impact on health systems and population health globally. To combat the spread of COVID-19, countries enacted guidelines and safety measures, including testing, contact tracing, and quarantine. It was unclear the extent to which uptake of COVID-19 testing and other health initiatives would be accepted in countries with a history of dealing with widespread communicable disease transmission such as HIV or Tuberculosis. The objective of this study was to understand and compare the facilitators and barriers to COVID-19 testing at hospital sites in two rural communities in Lesotho and community spaces (referred to as hubs) in one urban community in Zambia during active phases of COVID-19 pandemic. Individual interviews and focus group discussions (FGDs) were held during March-October 2021 to explore facilitators and barriers to COVID-19 testing. FGDs with 105 community members and health care workers, and 16 individual interviews with key informants and four mystery shoppers were conducted across the two countries. In Zambia, four mystery shopper observations, and eight hub observations were also conducted. Individual country codebooks were developed and combined; thematic analyses were then conducted using the combined codebook. Findings were compared across the two countries, and most were consistent across the two countries. Two primary themes emerged that related to both barriers and facilitators: (1) structural conditions; (2) social implications and attitudes. The structural conditions that operated as barriers in both countries included public health isolation measures and misinformation. In Lesotho, the cost of tests was an additional barrier. The only structural facilitators were in Zambia where the community hubs were found to be accessible and convenient. The social implication barriers related to fear of isolation, stigma, and mental health implications because of quarantine, perceived pain of the test, and compromised privacy. Social facilitators that led to people testing included experiencing COVID-19 firsthand and knowing people who had died because of COVID-19. Across both countries, primary barriers and facilitators to COVID-19 related to structural conditions and social implications and attitudes. Public health measures can be at odds with social and economic realities; pandemic response should balance public health control and the socio-economic needs. Data from Zambia revealed that community-based settings have the potential to increase uptake of testing services. Community-based campaigns to normalize and reduce stigma for COVID-19 testing services are needed.